Don't touch: Developmental trajectories of toddlers' behavioral regulation related to older siblings' behaviors and parental discipline. Issue 4 (10th February 2020) - van Berkel, Sheila R.; Song, Ju‐Hyun; Gonzalez, Richard; Olson, Sheryl L.; Volling, Brenda L.
Abstract: Behavioral regulation is one of the key developmental skills children acquire during early childhood. Previous research has focused primarily on the role of parents as socializing agents in this process, yet it is likely that older siblings also are influential given the numerous daily interactions between siblings. This exploratory longitudinal study investigated developmental heterogeneity in behavioral regulation during toddlerhood and the early preschool years (18 to 36 months) and relations with older siblings' control and behavioral regulation while taking into account parental discipline. Toddlers were visited at home at 18, 24, and 36 months and observed during a gift‐delay task with their older sibling in 93 families. Behavioral regulation of both siblings and gentle and harsh control of the older sibling were coded during the sibling gift‐delay task, which was validated using parent‐reports of toddlers' internalized conduct. Analyses revealed five distinct developmental trajectories among toddlers' behavioral regulation, revealing different patterns of developmental multifinality and equifinality. Older siblings' harsh control and parental discipline differed across toddler trajectory groups. Older siblings' behaviors covaried with the toddlers' behavioral regulation suggesting that older siblings may be acting as models for younger siblings, as well as disciplining and teaching toddlers to resist temptation.